1999
DOI: 10.1093/hmg/8.4.683
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Genes in the Center of the 11p15 Imprinted Domain Escape Genomic Imprinting

Abstract: We previously reported the isolation of a 2.5 Mb tumor-suppressing subchromosomal transferable fragment (STF) from human chromosome 11p15 and the identification of nine known genes and four novel genes within this STF. We now report the isolation of two novel cDNAs, designated here as TSSC4 and TSSC6 (tumor-suppressing STF cDNA 4 and 6), located within the STF. TSSC4 and TSSC6 encode predicted proteins of 329 and 290 amino acids, respectively, with no close similarity to previously reported proteins. TSSC4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…The TH gene has been isolated and mapped to chromosome 11p15.5 (Craig et al 1986;Moss et al 1986). This region contains at least seven imprinted genes (Lee et al 1999) which is intriguing, as imprinted genes tend to cluster. Also, the 5Ј flanking region of the TH gene is known to be methylated (Okuse et al 1997), methylation being a putative process involved in imprinting.…”
Section: Integrating Our Results With Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The TH gene has been isolated and mapped to chromosome 11p15.5 (Craig et al 1986;Moss et al 1986). This region contains at least seven imprinted genes (Lee et al 1999) which is intriguing, as imprinted genes tend to cluster. Also, the 5Ј flanking region of the TH gene is known to be methylated (Okuse et al 1997), methylation being a putative process involved in imprinting.…”
Section: Integrating Our Results With Existing Workmentioning
confidence: 99%
“…The TH gene has been isolated and mapped to chromosome 11p15.5 (Craig et al 1986;Moss et al 1986). This region contains at least seven imprinted genes (Lee et al 1999) which is intriguing, as imprinted genes tend to cluster. Also, the 5Ј NEUROPSYCHOPHARMACOLOGY 2002-VOL.…”
mentioning
confidence: 99%
“…Genes subject to genomic imprinting are typically clustered in a region of hundreds of kilobases (Greally et al, 1998;Lee et al, 1999;Rainier et al, 1993). One of these regions is located on chromosome 11p15 and contains a large domain of imprinted genes with growth-promoting (IGF2) and control (p57 kip2 and H19) functions (Chung et al, 1996;Dao et al, 1999;Lee et al, 1999;Sabbioni et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One of these regions is located on chromosome 11p15 and contains a large domain of imprinted genes with growth-promoting (IGF2) and control (p57 kip2 and H19) functions (Chung et al, 1996;Dao et al, 1999;Lee et al, 1999;Sabbioni et al, 1997). IGF2, a 67-amino acid peptide, is a paternally expressed insulinlike growth factor with autocrine growth function.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we and others have found that human chromosomal band 11p15 contains at least eight imprinted genes concentrated in an ∼1-Mb domain, of which six are expressed from the maternal allele and two are expressed from the paternal allele (Feinberg 1999). The organization of this domain is somewhat complicated in that we have identified two separate subdomains that are imprinted, separated by a region of three genes that appear to escape imprinting (Lee et al 1998(Lee et al , 1999. The boundaries of the overall 11p15 imprinted domain are known at both centromeric and telomeric ends because of the presence of at least eight nonimprinted genes that extend beyond the imprinted domain, including NAP2 and NUP98 on the centromeric side, and L23MRP and CTDS on the telomeric side (Rachmilewitz et al 1993;Tsang et al 1995;Hu et al 1996Hu et al , 1997Zubair et al 1997).…”
mentioning
confidence: 99%